Evaluation of Fillers Dispersion Degree in Elastomeric Magnetic Composites. (2nd May 2012) - Kruželák, Ján; Ilisch, Sybill; Hudec, Ivan; Dosoudil, Rastislav
Abstract : Elastomeric magnetic composites were prepared by incorporation of strontium ferrite into polymer matrices based on natural as well as butadiene rubber. Besides the rubber and ferrite, or the combinations of ferrite and carbon black (in case of natural rubber), the model rubber compounds contained only ingredients which support curing process. The study was dedicated to the observation of fillers dispersion degree in the rubber matrices and investigation of physical-mechanical and magnetic properties of prepared composites. The results indicate that the dispersion degree of ferrite in the rubber matrices is not very high, but it can be positively influenced by the addition of carbon black. Despite of the fact that ferrite exhibits only low reinforcing effect on cross-linked elastomeric materials, physical-mechanical properties can be also positively influenced by the mutual change in combinations of both fillers (ferrite and carbon black). The prepared materials seem to have suitable magnetic and elastic properties.